Gluteus Medius Muscle Activation During Isometric Muscle Contractions - O'Dwyer, C.; Sainsbury, David; O'Sullivan, Keiran (Human Kinetics Publishers INC, 2011)
Context: Functional subdivisions are proposed to exist in the gluteus medius (GM) muscle. Dysfunction of the GM, in particular its functional subdivisions, is commonly implicated in lower limb pathologies. However, there is a lack of empirical evidence examining the role of the subdivisions of the GM. Objectives: To compare the activation of the functional subdivisions of the GM (anterior, middle, and posterior) during isometric hip contractions. Design: Single-session, repeated-measures observational study. Setting: University research laboratory. Participants: Convenience sample of 15 healthy, pain-free subjects. Intervention: Subjects performed 3 maximal voluntary isometric contractions for hip abduction and internal and external rotation on an isokinetic dynamometer with simultaneous recording of surface electromyography (sEMG) activity of the GM subdivisions. Main Outcome Measures: sEMG muscle activity for each functional subdivision of the GM during each hip movement was analyzed using a 1-way repeated-measures ANOVA (post hoc Bonferroni). Results: The response of GM subdivisions during the 3 different isometric contractions was significantly different (interaction effect; P = .003). The anterior GM displayed significantly higher activation across all 3 isometric contractions than the middle and posterior subdivisions (main effect; both P < .001). The middle GM also demonstrated significantly higher activation than the posterior GM across all 3 isometric contractions (main effect; P = .027). There was also significantly higher activation of all 3 subdivisions during both abduction and internal rotation than during external rotation (main effect; both P < .001). Conclusions: The existence of functional subdivisions in the GM appears to be supported by the findings. Muscle activation was not homogeneous throughout the entire muscle. The highest GM activation was found in the anterior GM subdivision and during abduction and internal rotation. Future studies should examine the role of GM functional subdivisions in subjects with lower limb pathologies.